A Case of Cefixime, Ofloxacin Combination Tablet Induced Erythematous Macules - Dass, Prashant; Gulabani, Michell Michell; Raikar, Shrinivas (Indian Journal of Pharmacy Practice)
Erythematous macule is a type of rash which is associated with many dermatological conditions. We present a case of erythematous macules induced by administration of cefixime + ofloxacin tablet, its treatment and management. A seventeen year old female patient reported to us with a presentation of rash with scaling and itching for three days. On administration of the drug, the patient described a sensation of itching and discomfort on her entire body. The duty doctor attended the patient and immediately stopped the further administration of the offending medication. The patient was infused intravenous (iv) Dexamethasone 4 mg/ml and iv Pheniramine Maleate 1 ampoule (25 mg in 2 ml) immediately. The patient reported back in for follow-up and was without any residual rashes or other such complaints. She was advised to remember and refrain from the use of drugs in the offending class.
Keywords: Allergy; Cefixime; Erythema; Fever; Ofloxacin; Macule